The Karakteristik biofisik pantai peneluran penyu lekang (Lepidochelys olivacea) di Kampung Makimi, Distrik Makimi, Kabupaten Nabire - H. Lidan, Marry; Boli, Paulus; Kaber, Yuanike; F. Pattiasina, Thomas; Y. S. Purba, Gandi (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: The coastal area of Makimi Village, Makimi District, Nabire Regency is an important nesting site for the olive ridley turtle (Lepidochelys olivacea) with unique characteristics as its nests are located near residential areas that help protect the nesting sites. This research aims to determine the physical and biological parameters of the olive ridley turtle nesting habitat in Makimi Village, Makimi District, Nabire Regency. The research was conducted during the nesting season from February 1 to August 31, 2023. The results showed that The physical characteristics of Makimi Village Beach include an average beach width of 30 m, with a beach category ranging from sloping (6-39°) to steep (with a slope greater than 40°). The most common substrate in the nesting area is fine sand (60.05%), followed by very fine sand (25.77%). There were 11 nesting holes with temperatures ranging from 27°C to 31°C, with an average of 28.12°C to 30.87°C. The pH levels ranged from 5.5 to 7, and the average humidity was between 50% and 74%. The types of beach vegetation in the olive ridley turtle nesting area are dominated by six plant species: goat's foot creeper (Ipomoea pescaprae), waru tree (Hibiscus tiliaceus), pongam tree (Pongamia pinnata), sea almond (Terminalia catappa), coastal she-oak (Casuarina equisetifolia), and coconut palm (Cocos nucifera).